Expectation-based interventions for expatriates - Gibson,C.; Hardy,Jay; Baur,J.; Frink,D.; Buckley,M. R. (International Journal of Intercultural Relations, 2015)
Expatriate assignments are one of the primary tools used by organizations to extend their influence on an international level. While potentially of great value if they succeed, there are significant costs to both the organization and individual if they do not. Because of the high risk nature of expatriate assignments, there has been significant interest in interventions to increase the likelihood of their success. One under-explored area in the expatriate literature relates to expatriate expectations and acculturation experiences. We first review the literature regarding the major expectation-based interventions, including realistic job previews (RJPs), realistic living condition previews (RLCPs), and expectation lowering procedures (ELPs), and then develop a theoretical model of these interventions in the context of expatriates. Building upon this model, we suggest several important theoretical and practical questions that deserve future attention.
Keywords: Management